Documents relating to research for articles by Florence O’Donoghue, with enclosures on ambushes during the War of Independence at Crossbarry, Kilmichael, Upton, etc., - O'Donoghue, Florence, 1895-1967 (1951)
Includes copy documents, statements by those involved in ambushes and responses to draft articles by O'Donoghue.